Lipid droplet biogenesis regulated by the FgNem1/Spo7-FgPah1 phosphatase cascade plays critical roles in fungal development and virulence in Fusarium graminearum - Liu, Na (The New phytologist, 2019)
© 2019 The Authors. New Phytologist © 2019 New Phytologist Trust.